2000
DOI: 10.1075/jgl.1.03arv
|View full text |Cite
|
Sign up to set email alerts
|

The phonetics of stress in Greek

Abstract: This paper reports on two experiments that investigate the acoustic correlates of primary stress in Greek. The results clearly show that the most robust correlate is amplitude integral, a measurement that combines those of duration and (average) amplitude, and thus is closer to the perceptual property of prominence that characterises stressed syllables. The paper also discusses the role of pitch in signalling stress, by presenting new and re-analysing existing data on this issue. The significance of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Beyond this constraint there are no known phonological restrictions as to which vowels or syllable types may carry stress, so stress is phonologically unpredictable (making Greek a language with a lexical accent system; Revithiadou, 1999). Stressed vowels stand out phonetically by being longer and louder than unstressed vowels (Arvaniti, 2000(Arvaniti, , 2007. Unstressed vowels exhibit only limited centralization (i.e., tendency to neutral articulation) and, crucially, there is no phonological vowel reduction associated with lack of stress (Arvaniti, 2007;Fourakis, Botinis, & Katsaiti, 1999).…”
Section: Knaus El Shanawany Wiese Knaus Wiese Janßen Rothermichmentioning
confidence: 99%
“…Beyond this constraint there are no known phonological restrictions as to which vowels or syllable types may carry stress, so stress is phonologically unpredictable (making Greek a language with a lexical accent system; Revithiadou, 1999). Stressed vowels stand out phonetically by being longer and louder than unstressed vowels (Arvaniti, 2000(Arvaniti, , 2007. Unstressed vowels exhibit only limited centralization (i.e., tendency to neutral articulation) and, crucially, there is no phonological vowel reduction associated with lack of stress (Arvaniti, 2007;Fourakis, Botinis, & Katsaiti, 1999).…”
Section: Knaus El Shanawany Wiese Knaus Wiese Janßen Rothermichmentioning
confidence: 99%
“…In recent years, there have been a number of acoustic studies of stress in Greek, however, their findings are not consistent with regard to the defining properties of stress in this language. Thus, we find the claim in some studies that greater duration is a crucial stress cue (e.g., Dauer 1980;Botinis 1989;Arvaniti 2000;Fourakis et al 1999;Nicolaidis and Rispoli 2005;Nicolaidis and Sfakianaki 2007;Baltazani 2007). Vowel centralization is also presented as a significant property in a number of studies, with unstressed vowels being more centralized than stressed ones (e.g., Fourakis et al 1999;Nicolaidis and Rispoli 2005;Baltazani 2007;Nicolaidis and Sfakianaki 2007).…”
Section: Acoustic Properties Of Stress In Modern Greekmentioning
confidence: 91%
“…Botinis (1989) and Arvaniti (2000) showed that stressed vowels have higher amplitude than unstressed vowels and are 30% to 40% longer. However, neither duration nor amplitude are consistently greater in stressed versus unstressed vowels and syllables.…”
Section: Lexical Stress In Greekmentioning
confidence: 99%
“…However, neither duration nor amplitude are consistently greater in stressed versus unstressed vowels and syllables. Accordingly, it is argued that amplitude integral, a measure that combines the effect of amplitude and duration, is a more representative correlate of stress in Greek (Arvaniti, 2000;2007) than any one single measure.…”
Section: Lexical Stress In Greekmentioning
confidence: 99%